Pleistocene phylogeography and cryptic diversity of a tiger beetle, Calomera littoralis, in North-Eastern Mediterranean and Pontic regions inferred from mitochondrial COI gene sequences - Jaskuła, Radomir (PeerJ, 2016)
Background. Calomera littoralis is a Palearctic species, widely distributed in Europe; inhabiting predominantly its Atlantic, Mediterranean and Black Sea coastlines. Methods. Its phylogeography on the Balkan Peninsula and on the north-western Black Sea coast was inferred using a 697 bp long portion of the mitochondrial COI gene, amplified from 169 individuals collected on 43 localities. Results. The results revealed two genetically divergent groups/lineages, the southern one inhabiting both the Balkan Peninsula and the Pontic Region and the northern one found exclusively in the Pontic Region. Species delimitation based on DNA barcoding gap suggested an interspecific level of divergence between these groups. Multivariate analysis of eight male and female morphometric traits detected no difference between the groups, implying they may represent cryptic species. The Bayesian time-calibrated reconstruction of phylogeny suggested that the lineages diverged ca. 2.3 Ma, in early Pleistocene. Discussion. The presence of the two genetically divergent groups results most likely from contemporary isolation of the Pontic basin from the Mediterranean that broke the continuous strip of coastal habitats inhabited by C. littoralis. Demographic analyses indicated that both lineages have been in demographic and spatial expansion since ca. 0.15 Ma. It coincides with the terminal stage of MIS-6, i.e., Wartanian/Saalian glaciation, and beginning of MIS-5e, i.e., Eemian interglacial, during which, due to eustatic sea level rise, a wide connection between Mediterranean and the Pontic basin was re-established. This, along with re-appearance of coastal habitats could initiate north-east expansion of the southern lineage and its secondary contact with the northern one. The isolation of the Pontic basin from the Mediterranean during the Weichselian glaciation most likely did not have any effect on their phylogeography.